2022
DOI: 10.3389/fendo.2022.977347
|View full text |Cite
|
Sign up to set email alerts
|

MiR-539-3p impairs osteogenesis by suppressing Wnt interaction with LRP-6 co-receptor and subsequent inhibition of Akap-3 signaling pathway

Abstract: X-linked hypophosphatemia (XLH), an inheritable form of rickets is caused due to mutation in Phex gene. Several factors are linked to the disease’s aetiology, including non-coding RNA molecules (miRNAs), which are key post-transcriptional regulators of gene expression and play a significant role in osteoblast functions. MicroRNAs sequence analysis showed differentially regulated miRNAs in phex silenced osteoblast cells. In this article, we report miR-539-3p, an unidentified novel miRNA, in the functional regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…MiR-539-3p targets not only Igf1r and Lrp6 genes but also Akap3, Rnf2, and Adamts5 genes, as reported in previous studies [33,39,40]. Our current study revealed that feeding the LC-HP diet downregulated hippocampal mRNA levels of Akap3, while no significant changes were observed in Rnf2 or Adamts5 mRNAs (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…MiR-539-3p targets not only Igf1r and Lrp6 genes but also Akap3, Rnf2, and Adamts5 genes, as reported in previous studies [33,39,40]. Our current study revealed that feeding the LC-HP diet downregulated hippocampal mRNA levels of Akap3, while no significant changes were observed in Rnf2 or Adamts5 mRNAs (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Of particular interest was miR-539-3p, as it is also predicted to target pathways related to IGF-1R. Previous research has demonstrated that miR-539-3p downregulates Lrp6 mRNA levels [33], and LRP6, in turn, regulates expressions and activation of IGF-1R [34,35]. LRP6 plays a critical role in Wnt/β-catenin signal transduction [3638].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pepe et al ( 55 ) discovered that extracellular vesicle-derived miR-1246 is linked to osteoclast differentiation. Tripathi et al ( 62 ) found that miR-539 is related to the regulation of osteoblastogenesis. Based on this evidence, it is inferred that the aberrant expression of hsa-miRNA-27a-5p, hsa-miRNA-539-5p, and hsa-miRNA-1246 in AIS patients may be associated with the progression of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…The luciferase reporter gene assay indicated that miR-539-3p could bind to CCAT2 and BMI1. Previous studies have indicated that miR-539-3p can regulate chondrogenic differentiation, 40) osteoblast functions, 41) and tumor progression. 42) Additionally, miR-539-3p was upregulated after I/R injury, and its overexpression exerted detrimental effects on myocardial I/R injury.…”
Section: Discussionmentioning
confidence: 99%